Embryonic lethality and defective mammary gland development of activator‐function impaired conditional knock‐in Erbb3V943R mice. Issue 1 (5th December 2020) - Senger, Kate; Yuan, Wenlin; Sagolla, Meredith; Doerr, Jonas; Bolon, Brad; Ziai, James; Sun, Kai‐Hui; Warming, Soren; Roose‐Girma, Merone; Zhang, Na; Tam, Lucinda; Newman, Robert J.; et al.
Abstract: ERBB3 is a pseudokinase domain‐containing member of the ERBB family of receptor tyrosine kinases (RTKs). Following ligand binding, ERBB receptors homo‐ or hetero‐dimerize, leading to a head‐to‐tail arrangement of the intracellular kinase domains, where the "receiver" kinase domain of one ERBB is activated by the "activator" domain of the other ERBB in the dimer. In ERBB3, a conserved valine at codon 943 (V943) in the kinase C‐terminal domain has been shown to be important for its function as an "activator" kinase in vitro . Here we report a knock‐in mouse model where we have modified the endogenous Erbb3 allele to allow for tissue‐specific conditional expression of Erbb3 V943R ( Erbb3 CKI‐V943R ). Additionally, we generated an Erbb3 D850N ( Erbb3 CKI‐D850N ) conditional knock‐in mouse model where the conserved aspartate in the DFG motif of the pseudokinase domain was mutated to abolish any potential residual kinase activity. While Erbb3 D850N/D850N animals developed normally, homozygous Erbb3 V943R/V943R expression during development resulted in embryonic lethality. Further, tissue specific expression of Erbb3 V943R/V943R in the mammary gland epithelium following its activation using MMTV‐Cre resulted in delayed elongation of the ductal network during puberty. Single‐cell RNA‐seq analysis of Erbb3 V943R/V943R mammary glands showed a reduction in a specific subset of fibrinogen‐producing luminal epithelial cells. Abstract : ERBB3 receptor tyrosine kinase, a member of the ERBB family, has an important role in development and disease. It is the only member of the ERBB family with a pseudokinase domain and it preferentially heterodimerizes with ERBB2 to activate ERBB2 through allosteric kinase domain interactions. While targeted replacement of a conserved amino acid that abolishes its residual protein kinase activity was consistent with life and normal development, replacement of a residue essential for activator‐receptor interactions showed embryonic lethality and delayed ductal elongation in the developing mutant mammary gland. Single cell analysis of the targeted mammary glands showed reduction in a specific subset of fibrinogen‐producing luminal epithelial cells, suggesting that these cells are dependent on ERBB3‐mediated allosteric signaling.